International Commercial Arbitration: International Conventions, Country Reports and Comparative Analysis - Balthasar, Stephan (Verlag C.H.BECK Recht - Wirtschaft - Steuern, 2021)
Balthasar International Commercial Arbitration The Handbook is a unique combination of international and domestic sources of arbitration law and practice. It provides detailed commentary on the global framework of international commercial arbitration, in particular the New York Convention, the UNCITRAL Model Law, and international investment treaties. In addition, it gives comprehensive insight into international arbitration laws of countries covering over 60% of the global economy: Austria, Belgium, Brazil, China, England and Wales, France, Germany, Hong Kong, India, the Netherlands, Russia, Singapore, Spain, Sweden, Switzerland, and the U.S. The new edition includes numerous references to recent case law, material and legislative reform as well as topical developments in areas such as arbitrators’ jurisdiction, the conduct of arbitral proceedings and the judicial control of arbitral awards.